Effect of circulating anti-Mullerian hormone on the reproductive potential of gilts - Xia, Wei; Zhou, Zhenmin; Cheng, Linghua; Fang, Xiaohuan; Tao, Chenyu; Qi, Yatian; Yu, Yang; Zhang, Di; Tian, Xiaofeng; Gao, Zihao; Bai, Jiahua; Wen, Junhui; et al. (Frontiers in Veterinary Science, 2025)
IntroductionDetermination of the ovarian follicular reserve is of great value for predicting fertility, while circulating anti-Müllerian hormone (AMH) plays an important role in maintaining the ovarian reserve.MethodsIn this study, we examined the effect of circulating AMH levels of gilts between 110 and 160 days of age on reproductive performance and evaluated the differences in the ovaries and uteruses of gilts with different AMH levels.ResultsThe results indicated a significant negative correlation between circulating AMH levels from days 110 to 160 and puberty (p < 0.05). Moreover, the total born, live born, and the herd retention rate across 3 successive parities were found to be higher in high-AMH gilts than in low-AMH ones. Uterine morphology was assessed, and it was found that high-AMH gilts had significantly increased uterine glandular density, and the median vascular area and the relative expression levels of FOXA2, VEGF, VEGFR, and CD31 were significantly increased (p < 0.05). Furthermore, high-AMH gilts had a greater number of antral follicles and higher expression levels in secondary and early antral follicles than low-AMH gilts (p < 0.05). To further explain this mechanism, RNA-seq analysis was performed, which indicated that differentially expressed genes (DEGs) of high-AMH gilt ovaries were enriched in pathways, including steroid hormone biosynthesis, arachidonic acid metabolism, and the gonadotropin-releasing hormone signaling pathway.DiscussionOur findings indicate that circulating AMH levels can possibly predict the reproductive potential of gilts, with day 160 circulating AMH levels being a potential predictive indicator.